Lurking in plain sight: Hypertension awareness and treatment among New York City taxi/for‐hire vehicle drivers - Narang, Bharat (J Clin Hypertens (Greenwich), 2020)
Hypertension is a risk factor for cardiovascular disease, which is the leading cause of death in the United States. Taxi and for‐hire vehicle (FHV) drivers, a largely male, immigrant and medically underserved population, are at increased risk of cardiovascular disease, in part due to the nature of their work. This study examined demographic and lifestyle predictors of hypertension diagnosis awareness, objectively measured blood pressure (hypertensive‐range vs non‐hypertensive‐range readings), medication use, and hypertension control. A cross‐sectional assessment was conducted with 983 male taxi/FHV drivers who attended health fairs in New York City from 2010 to 2017. Twenty‐three percent self‐reported a hypertension history and 46% had hypertensive‐range BP readings. Approximately, half the drivers lacked health insurance (47%) and a usual care source (46%). Thirty percent did not self‐report hypertension and had hypertensive‐range BP readings. Medication use was reported by 69% of hypertension‐aware drivers, and being older and having health care access (insurance, a usual care source, and seeing a doctor in the past year) was significantly associated with medication use. Hypertension‐unaware drivers with hypertensive‐range BP readings were less likely to have a usual care source. Over 60% of drivers who were hypertension‐aware and on medication had hypertensive‐range readings. There is a need for community‐based and workplace driver and provider interventions to address BP awareness and management and to provide health care navigation for vulnerable populations such as taxi/FHV vehicle drivers.